(untitled) - Lazarus, David (Tokyo, Japan, 1992)
It will tell you why Japan's largest manufacturer of bathroom fixtures designed a twin-seat toilet for use by both humans and cats. It will explain how a lingerie firm came to determine the bust size of the Statue of Liberty. It will examine the feeling of the man charged with looking after the bottled brains of some of the greatest minds the country has known.
Keywords: American literature; 20th century